Astragalus helanshanensis, a new plant species from the arid region of the Helan Mountains in northwestern China - Yang, Bo; Wang, Wenqiang; Wei, Siyu; Liang, Yongliang; Xu, Hao; Ma, Jinlian; Li, Xiaowei (Phytotaxa, 2025)
Astragalus helanshanensis is a newly identified species found on the floodplain fan at the southern end of the Helanshan Mountains in northwestern China. This leguminous plant is 3–5 cm in height, with extremely short, condensed stems and subappressed hairs throughout. Leaves 2–4 cm long; rachis persistent, leaflets always 2 pairs, mostly inserted on the upper 1/3 of petiole, opposite; 1–3 flowered; flag petal tips retuse, pterygoid limb notched; keeled limb 1/2 as long as petiole; pods ovate-elliptic, 10–12 mm long, densely covered with white subappressed hairs, bipinnate. The discovery of this species enriches the known diversity of Astragalus and provides a scientific basis for the ecological protection and utilization of these plant resources in the Helan Mountains, while further advancing our understanding of the evolution and ecology relationships of the Astragalus genus.